Enhancing Housing Finance for Socio-Economic Stability in Uzbekistan - Olim, Astanakulov; Balbaa, Mumhammad Eid; Mukhabbatkhon, Berdalieva; Batirova, Nilufar; Dadabaev, Umidjon (International Journal of Economics and Financial Issues, 2024)
This study is devoted to the analysis of the current state and prospects for improving housing finance in Uzbekistan in the period from 2018 to 2023. The purpose of the work is to identify key factors affecting the socio-economic stability of the country through the prism of housing sector development, and to develop practical recommendations for optimizing housing finance mechanisms. An analysis of the dynamics of key indicators of the housing sector in Uzbekistan for 2018-2023 revealed a positive trend in the growth of housing construction by 28.6% (from 12.3 million square meters in 2018 to 15.8 million square meters in 2023), an increase in the share of mortgage lending in the structure of housing finance from 23.4% to 41.7%, as well as an increase in the level of housing provision for the population increased from 15.9 sq.m. per person in 2018 to 17.4 sq.m. in 2023. At the same time, there are still imbalances in the territorial distribution of housing construction volumes and the availability of mortgage loans for various segments of the population. The econometric analysis showed that an increase in housing construction by 1% leads to an increase in GDP by 0.28%, and an increase in the share of mortgage lending by 1 percentage point contributes to a decrease in the unemployment rate by 0.14 percentage points.